2023
DOI: 10.1101/2023.07.19.23292904
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social Cohesion and Covid-19: an integrative review

Abstract: Background Nations of considerable wealth and sophisticated healthcare infrastructures have seen high rates of illness and death from Covid-19. Others with limited economic means and less developed healthcare infrastructures have achieved much lower burdens. In order to build a full understanding, an appraisal of the contribution of social relationships is necessary. Social cohesion represents a promising conceptual tool. Objective The aim was to examine scholarship on social cohesion during the Covid-19 pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 105 publications
0
1
0
Order By: Relevance
“…The authors argued that the experiences, framed mostly as challenges, identified from the 46 articles were similar over time (∼20 years), geographic contexts, and pathogens and focused mostly on individual level concerns, similar to literature surrounding HCWs’ experiences during pandemic times, for example, in the context of mental health ( Ng et al, 2020 ; Spoorthy, 2020 ). Beyond the individual-level experiences, two concepts that tend to receive attention in the context of pandemics include social cohesion and community resilience, typically framed as having an influence on the ways in which pandemics play out in specific settings ( Jewett et al, 2021 ; Ware, 2023 ). Further, exploring the impact of structural aspects on pandemic progress in a variety of settings could help to identify system vulnerabilities and the socio-cultural supports in settings where resources are constrained ( Smith, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors argued that the experiences, framed mostly as challenges, identified from the 46 articles were similar over time (∼20 years), geographic contexts, and pathogens and focused mostly on individual level concerns, similar to literature surrounding HCWs’ experiences during pandemic times, for example, in the context of mental health ( Ng et al, 2020 ; Spoorthy, 2020 ). Beyond the individual-level experiences, two concepts that tend to receive attention in the context of pandemics include social cohesion and community resilience, typically framed as having an influence on the ways in which pandemics play out in specific settings ( Jewett et al, 2021 ; Ware, 2023 ). Further, exploring the impact of structural aspects on pandemic progress in a variety of settings could help to identify system vulnerabilities and the socio-cultural supports in settings where resources are constrained ( Smith, 2020 ).…”
Section: Introductionmentioning
confidence: 99%